Diversity of the genus Terebellides (Polychaeta: Trichobranchidae) in the Adriatic Sea with the description of a new species - Parapar, J.; Mikac, B.; Fiege, D. (Zootaxa, 2013)
Based on specimens collected during the sampling campaigns in the Northern Adriatic from 2003–2010, the diversity of genus Terebellides (Polychaeta; Trichobranchidae) was studied and three species are reported for the Northern Adriatic Sea: Terebellides gracilis Malm, 1874, Terebellides mediterranea spec. nov., and Terebellides stroemii Sars, 1835. Terebellides stroemii was the only species previously reported from the area. Terebellides gracilis is reported for the first time for the Mediterranean Sea and its geographical distribution is extended south. Terebellides mediterranea spec. nov., is characterised by the presence of long notopodia and notochaetae in the first thoracic chaetiger. These three species are compared to other Terebellides species described or reported from North Atlantic waters, and a key to Terebellides species of the North East Atlantic and Mediterranean is provided.
World Polychaeta Database (WPolyDb)